Consensus-based recommendations for strengthening emergency care at primary health care level: a Delphi study - Meghan Botes; Judith Bruce; Richard Cooke (Global Health Action, 2023)
Background Emergency care at a primary health care (PHC) level must be strengthened to reduce overall mortality and morbidity in any country. Developing recommendations for improvement in this area should take into consideration the context and nuances of the current emergency care system and primary health care context. Contribution to policy from the experts in the cross-cutting fields of PHC and emergency care is lacking. Objectives This study aims to evaluate the strengths and weaknesses of emergency care in primary health settings and develop consensus-based recommendations for the strengthening of emergency care at this level. Methods Using a modified Delphi technique, data were collected from various data sources to evaluate the strengths and weaknesses of emergency care at PHC level, from which recommendation statements were developed. These recommendations were proposed to a panel of experts using a Delphi survey to build consensus on 14 recommendations to strengthen emergency care at PHC level. Results Ten experts were recruited to participate (n = 10) with a response rate of 90% in round II and 80% in round III of Delphi. Recommendations broadly addressed the areas of education and training in emergency care, the role and placement of various actors, leadership in emergency care and the development of a national plan for emergency care. Consensus was reached in round II for 97.61% of the statements and after modification based on open-ended comments, 98.21% consensus was reached in round III. Conclusion Strengthening emergency care at primary and subsequent levels of health care requires a coordinated effort and mandate from authority in order to effect real change.